RELEVANSI NILAI INFORMASI AKUNTANSI DAN MODAL INTELEKTUAL PADA PERUSAHAAN INDEKS LQ45 DI BURSA EFEK INDONESIA - Putri, Ni Wayan Lilik Eka; Rasmini, Ni Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.01.TAHUN.2023, 2023)
This study aims to analyze the value relevance of accounting which proxied with earnings per share (EPS) and book value per share (BVPS) as well as value relevance of intellectual capital information. The test was carried out on companies that are members of the LQ45 Index Listed on the Indonesia Stock Exchange (IDX) during the 2018-2020 period. The sample selection used purposive sampling technique. The data collection method in this research is the documentation method. Data were analyzed using multiple linear regression analysis. This study found that earnings per share (EPS) and book value per share (BVPS) as well as intellectual capital information has value relevance. This research can support signal theory, clean surplus theory, and resource based theory (RBT) related to the relevance of the value of earnings per share (EPS) and book value per share (BVPS) as well as intellectual capital information. The research has implications for all parties who need information regarding value relevance of earnings per share (EPS) and book value per share (BVPS) as well as intellectual capital information of companies incorporated in the LQ45 Index